2021
DOI: 10.1016/j.jaccao.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tafamidis on Serum Transthyretin Levels in Non-Trial Patients With Transthyretin Amyloid Cardiomyopathy

Abstract: Background Transthyretin amyloid (ATTR) cardiomyopathy is slowed by tafamidis, which stabilizes the TTR molecule and reduces the formation of amyloidogenic oligomers. Stabilizers in clinical doses raise serum TTR, which may be a surrogate for the degree of stabilization. Objectives This study aims to determine, in a non-trial, unselected population of patients with ATTR cardiomyopathy, the effect of tafamidis on serum levels of TTR, and to compare these with published d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Prealbumin may be a useful marker to assess treatment efficacy. Compared with baseline, increased prealbumin concentration of a median of 7.5 mg/dL is observed with stabilizer drug therapy (mean increases from baseline of 50% with tafamidis-free salt and 53% with acoramidis) and on average a more than 80% reduction in prealbumin is observed following TTR-suppressing drug therapy (such as patisiran, vutrisiran, and eplontersen) . There are established staging systems for ATTR cardiomyopathy that incorporate cardiac biomarkers including troponin and natriuretic peptide levels (Mayo), estimated glomerular filtration rate and natriuretic peptides (National Amyloidosis Centre), or biomarker plus NYHA class and daily dose of loop diuretics expressed in furosemide equivalents in milligrams per kilogram (Columbia University) (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Prealbumin may be a useful marker to assess treatment efficacy. Compared with baseline, increased prealbumin concentration of a median of 7.5 mg/dL is observed with stabilizer drug therapy (mean increases from baseline of 50% with tafamidis-free salt and 53% with acoramidis) and on average a more than 80% reduction in prealbumin is observed following TTR-suppressing drug therapy (such as patisiran, vutrisiran, and eplontersen) . There are established staging systems for ATTR cardiomyopathy that incorporate cardiac biomarkers including troponin and natriuretic peptide levels (Mayo), estimated glomerular filtration rate and natriuretic peptides (National Amyloidosis Centre), or biomarker plus NYHA class and daily dose of loop diuretics expressed in furosemide equivalents in milligrams per kilogram (Columbia University) (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Tafamidis concentration after 12 months of therapy was also a predictor of response for male patients. Falk et al suggested that measurement of TTR level change post-Tafamidis might be a surrogate for stabilization and could be an accurate measure of drug efficacy ( 32 ). Other treatments such as RNA interference therapeutics are developing rapidly in this indication with, it seems for the moment, great efficacy ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…One obvious difference that might account for the more rapid cardiac progression of patients with TTR variants is the instability of the mutant TTR molecule, leading to a greater degree of breakdown and to a more amyloidogenic product. This hypothesis is supported by the lower levels of circulating TTR protein observed in patients with the familial TTR gene mutation, with a reversion to normal levels following therapy with a TTR stabilizer 4 . Nevertheless, while more rapid TTR breakdown may account for a more rapid disease progression in ATTRv compared to ATTRwt, it does not account for the fact that ATTRv is often associated with neuropathy, whereas proven amyloid neuropathy in ATTRwt is very uncommon.…”
Section: Figurementioning
confidence: 99%
“…This hypothesis is supported by the lower levels of circulating TTR protein observed in patients with the familial TTR gene mutation, with a reversion to normal levels following therapy with a TTR stabilizer. 4 Nevertheless, while more rapid TTR breakdown may account for a more rapid disease progression in ATTRv compared to ATTRwt, it does not account for the fact that ATTRv is often associated with neuropathy, whereas proven amyloid neuropathy in ATTRwt is very uncommon. There is no doubt that the clinical development of heart failure in ATTR cardiomyopathy of either form is due to massive myocardial amyloid infiltration, but neuronal amyloid infiltration is probably not the major underlying pathophysiologic mechanism for early symptomatic ATTRv neuropathy.…”
Section: This Article Refers To 'Prevalence Characteristics and Outco...mentioning
confidence: 99%